2005
DOI: 10.1097/00042737-200507000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hyperhomocysteinaemia, activated protein C resistance and prothrombin gene mutation in inflammatory bowel disease

Abstract: High homocysteine and high serum folate may be associated with low vitamin B12 levels in IBD patients. We did not find any association between a low APC ratio and the factor V Leiden mutation or high factor VIII levels. Both hyperhomocysteinaemia and a low APC ratio may contribute to an increased risk of thromboembolic disease in IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Similar results were obtained by Roblin et al who detected a 55.6% prevalence of hyperhomocysteinemia in patients with IBD [22]. This higher prevalence varied among the patient groups evaluated and the mean values were usually higher compared with healthy controls [23,24].…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were obtained by Roblin et al who detected a 55.6% prevalence of hyperhomocysteinemia in patients with IBD [22]. This higher prevalence varied among the patient groups evaluated and the mean values were usually higher compared with healthy controls [23,24].…”
Section: Discussionsupporting
confidence: 87%
“…It is present in approximately 2% of Caucasians, leads to greater prothrombin plasma levels (heterozygous carriers have about 30% higher PT levels than healthy controls), and increases the risk of venous thrombosis about threefold [38] . However, no definite association between this gene mutation and IBD has been detected in several studies [30,[33][34][35]39] . Presence of this mutation is found at a similar prevalence in IBD patients as well as in IBD patients with thrombosis [27,[32][33] .…”
Section: G20210a Prothrombin Gene Mutationmentioning
confidence: 98%
“…Patients with UC and CD are at risk of developing micronutrient deficiencies including folate, iron, vitamin D, and so forth, and require close nutritional monitoring (40). Many studies have found the elevated concentration of homocysteine in plasma and colonic mucosa of patients suffering from IBD (41). The homocysteine levels may be influenced by nutritional (folate, B 12 , and B 6 ), genetic and pharmacological factor in IBD.…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%